At Westonci.ca, we make it easy to get the answers you need from a community of informed and experienced contributors. Explore thousands of questions and answers from knowledgeable experts in various fields on our Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

Drag the tiles to the boxes to form correct pairs. Not all tiles will be used.

Match the circle equations in general form with their corresponding equations in standard form.

[tex]\[
\begin{array}{ll}
x^2 + y^2 - 4x + 12y - 20 = 0 & (x-6)^2 + (y-4)^2 = 56 \\
x^2 + y^2 + 6x - 8y - 10 = 0 & (x-2)^2 + (y+6)^2 = 60 \\
3x^2 + 3y^2 + 12x + 18y - 15 = 0 & (x+2)^2 + (y+3)^2 = 18 \\
5x^2 + 5y^2 - 10x + 20y - 30 = 0 & (x+1)^2 + (y-6)^2 = 46 \\
2x^2 + 2y^2 - 24x - 16y - 8 = 0 & x^2 + y^2 + 2x - 12y - 9 = 0
\end{array}
\][/tex]


Sagot :

Sure, let's match each circle equation in its general form to its corresponding equation in the standard form. We'll need to pair the equations correctly.

General Form Equations:
1. [tex]\( x^2 + y^2 - 4x + 12y - 20 = 0 \)[/tex]
2. [tex]\( x^2 + y^2 + 6x - 8y - 10 = 0 \)[/tex]
3. [tex]\( 3x^2 + 3y^2 + 12x + 18y - 15 = 0 \)[/tex]
4. [tex]\( 5x^2 + 5y^2 - 10x + 20y - 30 = 0 \)[/tex]

Standard Form Equations:
1. [tex]\( (x - 6)^2 + (y - 4)^2 = 56 \)[/tex]
2. [tex]\( (x - 2)^2 + (y + 6)^2 = 60 \)[/tex]
3. [tex]\( (x + 2)^2 + (y + 3)^2 = 18 \)[/tex]
4. [tex]\( (x + 1)^2 + (y - 6)^2 = 46 \)[/tex]

Here's the correct matching:

1. [tex]\( x^2 + y^2 - 4x + 12y - 20 = 0 \)[/tex]
- Corresponds to: [tex]\( (x - 6)^2 + (y - 4)^2 = 56 \)[/tex]

2. [tex]\( x^2 + y^2 + 6x - 8y - 10 = 0 \)[/tex]
- Corresponds to: [tex]\( (x - 2)^2 + (y + 6)^2 = 60 \)[/tex]

3. [tex]\( 3x^2 + 3y^2 + 12x + 18y - 15 = 0 \)[/tex]
- Corresponds to: [tex]\( (x + 2)^2 + (y + 3)^2 = 18 \)[/tex]

4. [tex]\( 5x^2 + 5y^2 - 10x + 20y - 30 = 0 \)[/tex]
- Corresponds to: [tex]\( (x + 1)^2 + (y - 6)^2 = 46 \)[/tex]

Our final pairs are:
1. [tex]\( x^2 + y^2 - 4x + 12y - 20 = 0 \)[/tex] → [tex]\( (x - 6)^2 + (y - 4)^2 = 56 \)[/tex]
2. [tex]\( x^2 + y^2 + 6x - 8y - 10 = 0 \)[/tex] → [tex]\( (x - 2)^2 + (y + 6)^2 = 60 \)[/tex]
3. [tex]\( 3x^2 + 3y^2 + 12x + 18y - 15 = 0 \)[/tex] → [tex]\( (x + 2)^2 + (y + 3)^2 = 18 \)[/tex]
4. [tex]\( 5x^2 + 5y^2 - 10x + 20y - 30 = 0 \)[/tex] → [tex]\( (x + 1)^2 + (y - 6)^2 = 46 \)[/tex]